Site-specific morphological and nutritional variability of Caulerpa lentillifera in Malaysia: a chemometric approach for tropical aquaculture - Ahmad Nasir, Nor Atikah Husna; Yuswan, Mohd Hafis; Abd Karim Shah, Nor Nadiah; Abd Rashed, Aswir; Kadota, Kazunori; Abdullah Sani, Muhamad Shirwan; Ismail, Mohd Fakhrulddin; Al-Awaadh, Alhussein M.; Riaz, Mian Nadeem; Yusof, Yus Aniza (Universiti Putra Malaysia Press, 2026)
Caulerpa lentillifera is an important tropical green macroalgae cultivated and harvested across Southeast Asia. Nevertheless, its morphological and biochemical responses towards varying environmental conditions remain insufficiently discussed. This study aimed to characterise the site-specific morphological, nutritional, and mineral variability of C. lentillifera collected from three Malaysian populations. Samples were harvested from wild populations in Port Dickson (PD) and Semporna (SS), and from a cultured pond population from Pulau Langkawi (PL). This study also applied chemometric methods to identify unique compositional patterns relevant to tropical aquaculture. Morphological and proximate analyses found that the PL sample has an assimilator length of up to 94 mm and a moisture content of 96% (wet weight basis), whereas PD samples had higher total nitrogen content (1.36 mg/L), crude fiber (3.45 g/100 g), and rhizoid length (13.8 mm), indicating site-related variability. Principal Component Analysis (PCA), Partial Least Squares Discriminant Analysis (PLS-DA), and hierarchical heatmaps were used to integrate water-quality, morphometric, nutritional, mineral, and heavy-metal datasets and to visualise site-specific clustering patterns. The PCA explained 62.5% of the total variance, and the PLS-DA model showed clear, yet descriptive, group separation (R² and Q² > 0.9; p = 0.001). The fibre, calcium, and carbohydrates were identified as the main discriminant factors. Overall, the analyses revealed distinct site-associated compositional trends rather than definitive classifications. These findings provide baseline insights to guide future site selection and cultivation strategies for sustainable tropical aquaculture.